Many voices, one ideal the campaign for independence in the Philippines, 1921-1927 - Hofilena, Josefina Dalupan 1960- (2006)
During the administration of Governor-General Leonard Wood (1921-1927), the ideal of independence dominated the national consciousness of both the leaders and the people and represented the highest aspiration of Filipino society. To achieve independence, Filipinos sought to enlarge the extent of their political power and ensure a greater share of domestic autonomy. Any contraction in the scope of autonomy would would be countered by the Filipino leadership and would lead to an intensification of the nationalist struggle for independence. with each defense of their hard-won political gains against a Governor-General who sought to give them only what the Jones Law gave, the nacionalista leadership raised the battle cry of independence and stirred up a nation behind it. This political struggle was dominated by the voices of Manuel L. Quezon, Sergio Osmeña, and other leading voices of the Filipino people. As leaders of the party in power they claimed to speak for the Filipino people, to give form to the people's deepest desires. There were other political voices as well, particularly those of the minority Partido Democrata, who--like the nacionalistas-advocated independence but rejected the manner in which the majority party sought to achieve it.But the struggle for political power by the Filipino elected leadership-whether nacionalista or democrata-was not the sole expression of Filipino nationalism during the Wood administration. Rather, the aspiration for independence was at the very heart of Filipino national identity and as such, the desire for independence crossed political, social, and gender boundaries. This sturdy is a search for, and a resonation of, the "other voices" in our country's history. It is an invitation to listen to what ordinary Filipinos of the 1920s said and felt about the most important issue of their day-the country's future as an independent state. The present study is an attempt to examine the extent to which nationalist agitation for independence permeated Filipino society during the 1920s and to highlight various articulations of the independence ideal. Because American colonialism permitted a large measure of democratic self-rule, the ordinary Filipinos used the democratic processes at their disposal to espouse independence. Such democratic processes included participation in elections, mass rallies and demonstrations, and writing letters to the editor. The mobilization of sectoral organizations was another democratic process used by Filipinos to advance nationalist goals. The intensification of the independence campaign during the Wood administration coincided with--and even became fodder for-- an organized articulation along sectoral lines. University students, revolutionary veterans, pensionado alumni, labor federations, and woman's clubs organized themselves in their effort to lend a more forceful voice to various issues, not the least of which was the issue of the country's readiness and desire for independence. Also heard were discord ant voices--not in the sense of being anti-independence but more on the sense of disagreeing with the path to be taken to achieve independence. Foremost among these discordant voices was Gen. Emilio Aguinaldo's who, paradoxically, was the personification of Philippine independence in the eyes of many Filipinos. That independence was the one dream shared by Filipinos, is evident in the manner in which they came together in the years 1921-1927. It was the Filipino people who were called upon to contribute to the Liberty Fund Drive. It was they who wrote the many letters to newspaper editors, expressing their views on the threats to domestic autonomy. It was they who joined political demonstrations and monster meetings. It was they who gave substance to the plans and programs of the National Supreme Council. While it was true that there were many voices-speaking on how independence could be achieved and who might lead the country towards that goal-there was still only one ideal-independence.
Vita.
"March 2006."
Thesis (Ph.D.History)--University of the Philippines Diliman.
Keywords: Autonomy -- Philippines; Philippines -- History -- Autonomy and independence movements